Impact of an intensive care unit telemedicine program on a rural health care system - Zawada, Jr, Edward T; Herr, Patricia; Larson, Deanna; Fromm, Robert; Kapaska, David; Erickson, David (Postgraduate medicine, 2009)
We evaluated the impact of a 15-hospital, rural, multi-state intensive care unit (ICU) telemedicine program. Acute Physiology, Age, and Chronic Health Evaluation (APACHE III) scores, raw mortality rates, and actual-to-predicted length of stay (LOS) ratios and mortality ratios were used. Surveys evaluated program impact in smaller facilities and satisfaction of the physicians staffing the remote center. Smaller facilities' staff reported improvements in the quality of critical care services and reduced transfers. In regional hospitals, acuity scores increased (retention of sicker patients) while raw mortality was the same or lower. Length of stay ratios were reduced in these hospitals. In the tertiary hospital, actual-to-predicted ICU and hospital mortality and LOS ratios decreased.